Sexual Function and Sexual Frequency among Chinese Women in Hong Kong: Implications for Public Health Services - Nga Ng, Anna Hoi; Kam, Weng Boey (Universiti Kebangsaan Malaysia, 2015)
Female sexual dysfunction (FSD) is a public health problem because of its high prevalence and harmful impacts on women’s physical health, psychological well-being, and overall quality of life. The objective of this exploratory study was to identify risk factors of sexual dysfunction and assess the sexual function of Hong Kong Chinese women. Results were compared with findings on American women. A questionnaire survey was conducted to collect data via convenience sampling. Participants of the study (N = 1011) were women (aged 18 or above) from diverse demographic backgrounds. Sexual function of Hong Kong Chinese women was generally adequate, but significantly lower than that of American women. Women of older age (41 years old or above), lower education (primary or below), divorced, in menopause or with oophorectomy were at risk of FSD. Women at risk of FSD also exhibited a decline of sexual frequency which implicated poor sexual health. With the risk factors identified, public health professionals could implement targeted health services that would tackle the problems of FSD in good time and promote the sexual health of women who are distressed by the problems.​